Legal Protection for Users in Securities Offerings Through the "Securities Crowdfunding" Crowdfunding Service - Saputra, Ade Rizki; Santoso, Aris Prio Agus; Suryadi, Agung (Formosa Journal of Sustainable Research, 2024)
Raising funds through crowdfunding services, especially in the form of securities crowdfunding, has experienced rapid development as an alternative for financing startups and small and medium enterprises (SMEs). In the United States, the Securities and Exchange Commission (SEC) has set up Regulation Crowdfunding (Reg CF) to oversee this practice, ensuring adequate protection for issuers and investors. However, legal protection in securities crowdfunding faces challenges in adapting to technological changes and market dynamics. This abstract explores the importance of effective regulation, education, and ongoing evaluation to ensure the sustainability of the crowdfunding ecosystem and user security in the future